2019
DOI: 10.1038/s41467-019-08360-5
|View full text |Cite
|
Sign up to set email alerts
|

Universal hidden order in amorphous cellular geometries

Abstract: Partitioning space into cells with certain extreme geometrical properties is a central problem in many fields of science and technology. Here we investigate the Quantizer problem, defined as the optimisation of the moment of inertia of Voronoi cells, i.e., similarly-sized ‘sphere-like’ polyhedra that tile space are preferred. We employ Lloyd’s centroidal Voronoi diagram algorithm to solve this problem and find that it converges to disordered states associated with deep local minima. These states are universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 66 publications
4
91
1
Order By: Relevance
“…(50), we see that the upper bound σ (2) U for these structures is exactly the same as σ e given by Eq. (63). Thus, we have rigorously demonstrated that anisotropic structures consisting of sets of intersecting parallel channels achieve the two-point anisotropic generalizations of the Hashin-Shtrikman bound (26) on σ e , regardless of whether they are ordered or disordered, hyperuniform or nonhyperuniform.…”
Section: Demonstration Of Optimality For Intersecting Parallel-channementioning
confidence: 78%
“…(50), we see that the upper bound σ (2) U for these structures is exactly the same as σ e given by Eq. (63). Thus, we have rigorously demonstrated that anisotropic structures consisting of sets of intersecting parallel channels achieve the two-point anisotropic generalizations of the Hashin-Shtrikman bound (26) on σ e , regardless of whether they are ordered or disordered, hyperuniform or nonhyperuniform.…”
Section: Demonstration Of Optimality For Intersecting Parallel-channementioning
confidence: 78%
“…Inflationary expansion explains why the primeval 10 90 causally-disconnected quantum “seeds” [ 31 ] led to the experimentally detected homogeneity and isotropy. Still, inflation would have amplified minute quantum fluctuations (pre-inflation) into slight density ripples of over- and under-density (post-inflation).Here the concept of hyperuniformity comes into play, i.e., the anomalous suppression of density fluctuations on large length scales occurring in amorphous cellular structures of ordered and disordered materials [ 55 ].The evolution of a given set of initial points takes place when, through Lloyd iterations, each point is replaced by the center mass of its Voronoi cell. This corresponds to a gradient descent algorithm which allows a progressive, general convergence to a random minimum in the potential energy surface.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to a gradient descent algorithm which allows a progressive, general convergence to a random minimum in the potential energy surface. Klatt et al [ 55 ] report that systems equipped with different initial configurations (such as, e.g., either hyper-fluctuating, or anisotropic, or relatively homogeneous point sets), converge towards the same high degree of uniformity after a relatively small number of Lloyd iterations (about 10 5 ).This means that, in the systems’ final states, independent of the initial conditions, the cell volumes become uniform and the dimension less total energy converges towards values comparable to the deep local energy minima of the optimal lattice. Therefore, we are allowed to describe the cosmic evolution suddenly after the Big Bang in terms of Lloyd iterations, where the initial quantum seeds stand for initial point sets, progressively converted to point sets with a centroidal Voronoi diagram.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their results verify that close loop power control supports the received SINR of OLPC to meet the target SINR by compensating the fading effect. 1 Following Slivnyak theorem, a typical user at origin leads to simplified statistical properties of an independent homogeneous Poisson point process (IHPPP) [9]. 2 The terms open loop power control and FPC are used interchangeably in this paper.…”
Section: B Related Workmentioning
confidence: 99%
“…In heterogeneous cellular networks (HetNets), coverage probability, spectrum efficiency, and throughput are significantly enhanced by enriching coverage area of macro base station (MBS) with small base station deployment (SBS D ) [1], [2]. In HetNets, MBS-associated users (MBS-AUs) and SBSassociated users (SBS-AUs) share the same frequency band and, hence, lead to high throughput.…”
Section: Introduction a Motivationmentioning
confidence: 99%